Implementation of Pancasila Values in Regional Head Leadership (Case Study: Hand of Love Assistance Program in the Leadership of Paulus Waterpauw 2020-2022 in West Papua Province) - Waterpauw, Paulus; Hanita, Margaretha; Runturambi, Arthur Josias Simon (Devotion : Journal of Research and Community Service, 2024)
The "Hand of Love (Bantuan Tangan Kasih) Assistance Program" under the leadership of Paulus Waterpauw from 2020-2022 in West Papua Province is investigated in this study. The data used here were firsthand information directly related to the implementation of the program and its implementation, along with documents, reports, and literature related to Pancasila values, regional leadership, and specific programs. The results of the research are discussed based on the policy implementation of Van Meter and Van Horn (1975), which emphasizes six dimensions, namely policy goals and objectives, policy resources, characteristics of implementing agents, implementing attitudes, communication between implementing organizations, and socio-economic and political environment. The findings show that the success of the implementation process of the Hand of Love Assistance Program is greatly influenced by the characteristics of the implementers. The hedonistic lifestyle after the enactment of the Special Autonomy has eroded the morality of almost some state administrators. The "hand of love" program is a program that has been implemented by a transmigration and labor office, Bank Penyalur, as the implementer.